Defining movement strategies in soccer instep kicking using the relationship between pelvis and kick leg rotations - Augustus, S.; Hudson, P.; Smith, N. (ISBS Proceedings Archive (Michigan), 2021)
The aim of this study was to examine the relationship between pelvis and kick leg rotation strategies during soccer instep kicking. Twenty semi-professional players performed kicks for maximal speed and accuracy. A strong relationship was shown between pelvis transverse rotation (i.e. speed of rotation of kick side hip towards the ball upon impact) and kick leg (i.e. thigh-knee angular velocity ratio upon impact) strategies (r = 0.760, p <0.001). Knowledge of a kicker`s preferred strategy can help inform technical and conditioning training recommendations for the individual. Pelvis maintainer-thigh dominant kickers might focus on developing the concentric capabilities of the hip flexors, whereas reverser-knee dominant kickers might benefit from developing the ability to decelerate the pelvis and thigh and induce motion-dependent angular acceleration of the lower leg towards the ball.